KOMUNIKASI EFEKTIF DAN FAKTOR PENENTU EFEKTIVITAS PERSUASI - Yudi Perbawaningsih (Jurnal Kependidikan, 2003)
Abstract Learning process is persuasive communication process. The effectiveness of persuasive depends on several factors such as the persuader, message, media, persuade. In learning process, the effectiveness depends on the credibility of the lecturer, quality of the learning material and the quality of media using. These factors could be predictors for the students’ learning achievement. This article is based on the research about the factors that influence the effectiveness of learning communication. Based on the survey research and quantitative data analysis, it was found that the factors, which influence the learning achievement, are the intellectual qualities that have already had by the students and the quality of the teaching materials. The credibility of the lecturers and the quality of the learning media utilizing influence learning achievement are only for the students who have low achievement and low learning motivation in class. Keywords: learning, communication, persuasion, effectiveness, predictor